Technique Anglaise : Current trends in British Art - Cooke, Lynne; Furlong, William; Gillick, Liam; Paley, Maureen; Renton, Andrew; Schubert, Karsten (London : One-Off Press Thames and Hudson London, 1991)
Bond, Henry ; Collishaw, Mat ; Counsell, Melanie ; Davenport, Ian ; Davey, Grenville ; Denis, Dominic ; Fairhurst, Angus ; Gallaccio, Anya ; Gillick, Liam ; Hansen, Markus ; Hirst, Damien ; Hume, Gary ; Landy, Michael ; Lane, Abigail ; Langlands & Bell ; Linke, Simon ; Lucas, Sarah ; Milroy, Lisa ; de Monchaux, Cathy ; Opie, Julian ; Patterson, Simon ; Roberts, Perry ; Robins, Tessa ; Russell, Caroline ; Whiteread, Rachel ; Williams, Gerard ; Wood, Craig
Biog., ind. tent., gr. tent., bibliog. p. 202-222
Engels
boek
Keywords: Groot-Brittannië; Verenigd Koninkrijk; Engeland